High-temperature-resistant and corrosion-resistant coating and preparation method thereof
By adding phenolic resin and modified filler to the epoxy resin coating, a high-temperature and corrosion-resistant coating was prepared, which solved the problem of aging of existing coatings under high temperature and ultraviolet conditions, and achieved the long-term anti-aging and corrosion-resistant properties of the coating.
Patent Information
- Application Number
- CN202510025668.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
Existing epoxy resin coatings are prone to aging and deforming under high temperature and ultraviolet irradiation, which affects its protective effect on the material. In addition, existing antioxidants are prone to migration or detachment, and cannot play an anti-aging role in the long term.
A high-temperature and corrosion-resistant coating is used, and its formulation includes epoxy resin, phenolic resin, modified filler, pigment, curing agent, accelerator and solvent. The modified filler is prepared by esterification reaction and chemical bonding, and has good compatibility and stability.
This coating has excellent and stable high temperature resistance, corrosion resistance, aging resistance and flame retardancy. It has a greatly extended service life. The modified filler is not easy to migrate or take off, and it plays a long-term anti-aging effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coatings, and in particular, relates to a high temperature resistant and corrosion resistant coating and a preparation method thereof. Background Art
[0002] The surface of the material is easily damaged by the temperature, humidity and acidity and alkalinity of the environment, which can render the material unusable. Therefore, it is necessary to spray a protective coating on the surface of the material to isolate the material from water vapor, oxygen, acid and alkali in the air to achieve a protective effect.
[0003] The coating prepared with epoxy resin as the base resin has good adhesion, low shrinkage, chemical resistance, simple process, strong adaptability, no pollution to the environment, etc. It has good adhesion to a variety of materials and has multiple functions such as sealing, insulation, anti-corrosion, and decoration. It is called a universal glue. However, epoxy resin coatings are prone to aging and deformation when used under high temperature and ultraviolet radiation conditions for a long time, which affects the protective effect of the coating on the material. Although adding antioxidants can protect the coating from aging to a certain extent, the antioxidants in the prior art are easy to migrate or come out, and cannot play an anti-aging role in the coating for a long time. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high temperature resistant and corrosion resistant coating and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high temperature resistant and anti-corrosion coating comprises the following raw materials in parts by weight: 40-50 parts of epoxy resin, 25-35 parts of phenolic resin, 20-30 parts of modified filler, 4-10 parts of pigment, 5-10 parts of curing agent, 0.5-1 part of accelerator and 50-65 parts of solvent.
[0006] Furthermore, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidyl ether epoxy resin, and alicyclic epoxy resin.
[0007] Phenolic resin is a linear resin formed by the condensation of phenol and formaldehyde. Phenolic resin has good wear resistance and excellent high temperature resistance. Even at very high temperatures, it can maintain its structural integrity and dimensional stability. Adding phenolic resin to the coating can effectively improve the high temperature resistance of the coating.
[0008] Furthermore, the modified filler is prepared by the following steps: S1. Blow nitrogen gas into a dry three-necked flask for 30 minutes to expel moisture and air in the flask, then add 4-(2H-benzotriazole-2-yl)-1,3-benzenediol and acetone, stir and heat to 40°C, then slowly add chloroacetyl chloride, keep the temperature at 40°C for 7 hours until no hydrogen chloride gas escapes, absorb the hydrogen chloride tail gas with sodium hydroxide alkaline solution, and desolventize after the reaction to obtain intermediate 1; the dosage ratio of 4-(2H-benzotriazole-2-yl)-1,3-benzenediol, chloroacetyl chloride and acetone is 34.1g:12.9mL:180mL; The molar ratio of 4-(2H-benzotriazole-2-yl)-1,3-benzenediol and chloroacetyl chloride is controlled to be 1:1.05-1.1, and then 4-(2H-benzotriazole-2-yl)-1,3-benzenediol and chloroacetyl chloride undergo esterification reaction under heating. The reaction process is as follows:
[0009] S2, nitrogen was blown into a dry three-necked flask for 30 minutes to expel air and moisture in the flask, and then intermediate 1, pyridine and dimethyl sulfoxide were added, stirred and dissolved, and the temperature was raised to 60°C, and 1,3-propylenediamine was slowly added. After the addition was completed, the temperature was kept at 60°C for 3 hours. After the reaction was completed, the reaction was cooled to room temperature and distilled under reduced pressure to obtain intermediate 2; the usage ratio of intermediate 1, 1,3-propylenediamine, pyridine and dimethyl sulfoxide was 39.5g:11.7mL:12.6mL:200mL; Pyridine is used as an acid-binding agent to control the molar ratio of intermediate 1 and 1,3-propylenediamine to be 1:1.05-1.1. The -Cl of intermediate 1 and the -NH2 of 1,3-propylenediamine undergo a substitution reaction under heating. The reaction process is as follows:
[0010] S3, nitrogen was blown into a dry three-necked flask for 30 minutes to expel air and moisture in the flask, and then intermediate 2, triethylamine and dimethyl sulfoxide were added, stirred and dissolved, and the temperature was raised to 70°C, and then 2,6-di-tert-butyl-4-bromomethylphenol was slowly added. After the addition was completed, the temperature was kept at 70°C for 4 hours. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dimethyl sulfoxide was 36.7g:29.9g:16.7mL:220mL; Triethylamine is used as an acid binding agent to control the molar ratio of intermediate 2 and 2,6-di-tert-butyl-4-bromomethylphenol to be 1.05-1.1:1. The -NH2 of intermediate 2 and the -Br of 2,6-di-tert-butyl-4-bromomethylphenol undergo a substitution reaction under heating. The reaction process is shown below:
[0011] S4, add intermediate 3 and DMF (N,N-dimethylformamide) to a dry three-necked flask, stir evenly and heat to 65°C, then slowly add KH560 (3-glycidyloxypropyltrimethoxysilane) under nitrogen protection, keep warm for 3 hours after the addition is complete, cool to room temperature after the reaction is completed, distill under reduced pressure, purify by column chromatography (select a mixed solvent of cyclohexane and ethyl acetate as the eluent, the volume ratio of cyclohexane and ethyl acetate is 1:1), distill under reduced pressure to obtain intermediate 4; the usage ratio of intermediate 3, KH560 and DMF is 45g:15.5mL:220mL; Under heating conditions, the molar ratio of intermediate 3 and KH560 is controlled to be 1.05-1.1:1, then -NH- of intermediate 3 reacts with the epoxy group of KH560, and the reaction process is as follows:
[0012] S5. Mix the filler and deionized water in a three-necked flask, then slowly add glacial acetic acid to adjust the pH to 4, then slowly add the mixed solution of intermediate 4 and DMF while stirring, heat to 65°C after the addition, keep warm for 1 hour, cool to room temperature after the reaction, centrifuge, take the lower layer of precipitate after centrifugation, ultrasonically disperse it in anhydrous ethanol for 30 minutes, and finally dry it at 80°C for 12 hours to obtain a modified filler; the amount ratio of filler, intermediate 4, DMF and deionized water is 42g:3g:20mL:250mL.
[0013] Furthermore, the filler is a mixture of titanium dioxide, aluminum hydroxide, magnesium hydroxide and glass flakes in a mass ratio of 1:(0-0.5):(0.5-1):(3-5).
[0014] The surfaces of titanium dioxide, aluminum hydroxide, magnesium hydroxide and glass flakes are rich in hydroxyl groups. Under heating and acidic conditions, the silaneoxy groups on the surface of intermediate 4 are hydrolyzed and chemically bonded with the hydroxyl groups on the surface of the filler to finally produce a modified filler.
[0015] Titanium dioxide can give the coating antibacterial and anti-ultraviolet aging properties; aluminum hydroxide and magnesium hydroxide can give the coating efficient and safe flame retardant and smoke suppression properties; titanium dioxide, aluminum hydroxide, and magnesium hydroxide can also work together to increase the gloss, adhesion, wear resistance, and hardness of the coating; glass flakes are arranged in parallel and overlapping palace structures in the coating, thus forming a dense anti-seepage layer structure. The penetration of the corrosive medium in the cured coating must go through countless tortuous paths. Therefore, in a certain thickness of coating, the distance of corrosion penetration is greatly extended, which is equivalent to effectively increasing the thickness of the glass flake anti-corrosion layer. Therefore, glass flakes can play a good anti-corrosion effect. The chemical interaction between intermediate 4 and the filler greatly improves the dispersion of the modified filler and the compatibility between the filler and the resin. The lipophilic benzene ring, ester group, and ether bond further improve the compatibility between the modified filler and the resin, and then the fillers such as titanium dioxide in the modified filler can fully play their role and improve the weather resistance, corrosion resistance, and flame retardancy of the coating.
[0016] The modified filler also contains benzotriazole structures and hindered phenol structures with anti-aging effects. The benzotriazole structure converts the energy of light into harmless energy and releases it by proton transfer. After absorbing ultraviolet light, the hydrogen bonds in the molecule are destroyed or become phototautomers, converting harmful ultraviolet rays into heat energy. It can absorb ultraviolet rays with a wavelength range of 200-400nm, effectively reducing the damage caused by ultraviolet rays to the coating; the hydroxyl group of the hindered phenol structure is restricted by spatial obstacles, and the hydrogen atom is easily detached from the original molecular structure, thereby achieving the effect of donating protons, and combining with peroxyl radicals, alkyl radicals, hydroxyl radicals, etc., causing them to lose their original activity, resulting in the termination of the aging reaction, and it has excellent antioxidant capacity. Therefore, the modified filler protects the coating from ultraviolet aging and thermal oxygen aging through the synergistic effect of inorganic antioxidants and organic antioxidant structures.
[0017] There are hydroxyl and amino groups on the surface of the modified filler, which can react chemically with the epoxy groups in the epoxy resin during the curing process, so that the epoxy resin and the modified filler are tightly bonded. This not only allows the modified filler to exist in the coating for a long time and always play an anti-aging, corrosion-resistant, flame-retardant and wear-resistant role, but also prevents liquids and gases from penetrating into the coating. The high temperature and corrosion resistance are even better, greatly extending the service life of the coating.
[0018] Furthermore, the pigment is one or more of iron oxide red, phthalocyanine blue, phthalocyanine green G, carbon black, and ultramarine.
[0019] Furthermore, the curing agent is one or more of dicyandiamide, isophoronediamine, and dodecanedicarboxylic acid dihydrazide.
[0020] Furthermore, the accelerator is one or more of 1-methylimidazole, 2-ethyl-4-methylimidazole, and 2-methylimidazole.
[0021] Furthermore, the solvent is one or more of ethanol, acetone, butanone, N,N-dimethylacetamide, and N,N-dimethylformamide.
[0022] A method for preparing a high temperature resistant and corrosion resistant coating comprises the following steps: Weigh each raw material by weight, then add epoxy resin, phenolic resin, modified filler, pigment and solvent into a disperser and stir thoroughly until mixed evenly, finally add curing agent and accelerator, stir thoroughly to obtain high temperature resistant and corrosion resistant coating.
[0023] The beneficial effects of the present invention are as follows: the modified filler contains inorganic fillers such as titanium dioxide, glass flakes, and benzotriazole structures and hindered phenol structures, and the modified filler has good compatibility with the other raw materials and has a chemical reaction with the epoxy resin, so the modified filler can stably exist in the coating, is not easy to migrate and fall out, and can play a role for a long time. In addition, with the combined effect of the other raw materials, the coating of the present invention has excellent and stable high temperature resistance, corrosion resistance, aging resistance, flame retardancy and other properties, and its service life is greatly extended. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1, preparing the modified filler, the specific steps are as follows: S1. Blow nitrogen gas into a 500 mL dry three-necked flask for 30 min to expel moisture and air in the flask, then add 34.1 g of 4-(2H-benzotriazole-2-yl)-1,3-diphenol and 180 mL of acetone, stir and heat to 40°C, then slowly add 12.9 mL of chloroacetyl chloride, keep the temperature at 40°C for 7 h until no hydrogen chloride gas escapes, absorb the hydrogen chloride tail gas with sodium hydroxide alkaline solution, and desolventize after the reaction to obtain intermediate 1; S2, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, then 39.5 g of intermediate 1, 12.6 mL of pyridine and 200 mL of dimethyl sulfoxide were added, stirred and dissolved, and the temperature was raised to 60°C, and then 11.7 mL of 1,3-propylenediamine was slowly added. After the addition was completed, the temperature was kept at 60°C for 3 h. After the reaction was completed, the reaction was cooled to room temperature and distilled under reduced pressure to obtain intermediate 2; S3, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, then 36.7 g of intermediate 2, 16.7 mL of triethylamine and 220 mL of dimethyl sulfoxide were added, stirred and dissolved, and the temperature was raised to 70°C, and then 29.9 g of 2,6-di-tert-butyl-4-bromomethylphenol was slowly added. After the addition was completed, the reaction was continued at 70°C for 4 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 3; S4, add 45g of intermediate 3 and 220mL of DMF into a 500mL dry three-necked flask, stir evenly and heat to 65°C, then slowly add 15.5mL of KH560 under nitrogen protection, keep warm for 3h after the addition is complete, cool to room temperature after the reaction is complete, distill under reduced pressure, purify by column chromatography (a mixed solvent of cyclohexane and ethyl acetate is selected as the eluent, and the volume ratio of cyclohexane and ethyl acetate is 1:1), and distill under reduced pressure to obtain intermediate 4; S5. Evenly mix 5.6 g titanium dioxide, 2.8 g aluminum hydroxide, 5.6 g magnesium hydroxide, 28 g glass flakes and 250 mL deionized water in a 500 mL three-necked flask, then slowly add glacial acetic acid to adjust the pH to 4, then slowly add 3 g intermediate 4 and 20 mL of DMF mixed solution while stirring. After the addition is complete, heat to 65 ° C and keep warm for 1 hour. After the reaction is completed, cool to room temperature and centrifuge. After centrifugation, take the lower layer of precipitate and ultrasonically disperse it in anhydrous ethanol for 30 minutes. Finally, dry it at 80 ° C for 12 hours to obtain a modified filler.
[0026] Example 2, preparing the modified filler, the specific steps are as follows: The remaining steps remain unchanged, except that the mass of titanium dioxide in step S2 is modified to 9.33 g, the mass of aluminum hydroxide is modified to 0 g, the mass of magnesium hydroxide is modified to 4.67 g, and the mass of glass flakes remains 28 g, thereby preparing a modified filler.
[0027] Example 3, preparing the modified filler, the specific steps are as follows: The remaining steps remain unchanged, except that the mass of titanium dioxide in step S2 is modified to 7g, the mass of aluminum hydroxide is modified to 2.8g, the mass of magnesium hydroxide is modified to 4.2g, and the mass of glass flakes remains 28g, thereby preparing a modified filler.
[0028] Example 4, preparing the modified filler, the specific steps are as follows: The remaining steps remain unchanged, steps S1 to S4 of Example 1 are removed, and the intermediate 4 in step S5 is replaced by 3-aminopropyltrimethoxysilane, thereby preparing a modified filler.
[0029] Example 5, preparing the coating, the specific steps are as follows: Weigh each raw material by weight, then add 40 parts of alicyclic epoxy resin, 25 parts of phenolic resin, 20 parts of modified filler prepared in Example 2, 4 parts of red iron oxide and 50 parts of N,N-dimethylacetamide into a disperser and stir thoroughly until mixed evenly, finally add 5 parts of isophorone diamine and 0.5 parts of 1-methylimidazole, stir thoroughly to obtain a high temperature resistant and corrosion resistant coating.
[0030] Example 6, preparing the coating, the specific steps are as follows: Each raw material is weighed by weight, and then 45 parts of glycidyl ether epoxy resin, 30 parts of phenolic resin, 27 parts of modified filler prepared in Example 3, 7 parts of phthalocyanine green G, 20 parts of ethanol and 40 parts of N,N-dimethylacetamide are added into a disperser and stirred until mixed evenly, and finally 8 parts of dodecane dicarboxylic acid dihydrazide and 0.8 parts of 2-ethyl-4-methylimidazole are added and stirred thoroughly to obtain a high temperature resistant and corrosion resistant coating.
[0031] Example 7, preparing the coating, the specific steps are as follows: Weigh each raw material by weight, then add 50 parts of bisphenol A epoxy resin, 35 parts of phenolic resin, 30 parts of modified filler prepared in Example 1, 10 parts of phthalocyanine blue, 15 parts of acetone and 50 parts of N,N-dimethylformamide into a disperser and stir thoroughly until mixed evenly, finally add 5 parts of dicyandiamide, 5 parts of dodecanedicarboxylic acid dihydrazide, 0.5 parts of 2-ethyl-4-methylimidazole and 0.5 parts of 2-methylimidazole, stir thoroughly to obtain a high temperature resistant and corrosion resistant coating.
[0032] Comparative Example 1, preparing the coating, the specific steps are as follows: The remaining steps remained unchanged, except that the modified filler in Example 5 was replaced by 2.67 parts of titanium dioxide, 1.33 parts of aluminum hydroxide, 2.67 parts of magnesium hydroxide and 13.33 parts of glass flakes, thereby preparing a coating.
[0033] Comparative Example 2, preparing the coating, the specific steps are as follows: The remaining steps remain unchanged, only the modified filler in Example 5 is replaced by the modified filler prepared in Example 4, thereby preparing the coating.
[0034] Comparative Example 3, preparing the coating, the specific steps are as follows: The remaining steps remain unchanged, except that the modified filler of Example 5 is replaced by 18.7 parts of the modified filler prepared in Example 4, 0.65 parts of the ultraviolet absorber UV-531 and 0.65 parts of the antioxidant 1010, thereby preparing a coating.
[0035] Performance Testing The coatings prepared in Examples 5-7 and Comparative Examples 1-3 were subjected to the following performance tests: (1) Corrosion resistance test: After the coating is applied on the copper foil and cured to form a coating with a thickness of 10-15 μm, the copper foil with the coating on the surface is immersed in an aqueous solution of acid (hydrochloric acid) and alkali (sodium hydroxide) with a temperature of 40°C and a concentration of 2 mol / L for 1 month to observe whether the copper foil has bubbles or spots.
[0036] (2) High temperature resistance test: After the coating is completely cured, weigh 15-20 mg of the sample and put it into a thermal gravimetric analyzer to test the decomposition temperature of the material at a heating rate of 10°C / min.
[0037] (3) Aging resistance test: After the coating is completely cured, the cured coating is cut into Type V dumbbell-shaped specimens according to ASTM-D638-03, boiled in boiling water and then dried. Five boiling and drying cycles are performed to test the tensile strength reduction rate of the material after heat aging; the specimens are cut into Type V dumbbell-shaped specimens and UV-aged for 120 h under a 30 W UV lamp to test the tensile strength reduction rate of the material after UV aging.
[0038] The test results of all items are shown in Table 1 below: Table 1 It can be seen from the test results in Table 1 above that the coatings prepared in Examples 5-7 of the present invention have more excellent anti-aging performance, corrosion resistance and high temperature resistance.
[0039] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0040] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high temperature resistant and anti-corrosion coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of epoxy resin, 25-35 parts of phenolic resin, 20-30 parts of modified filler, 4-10 parts of pigment, 5-10 parts of curing agent, 0.5-1 parts of accelerator and 50-65 parts of solvent; Wherein, the modified filler is prepared by the following steps: S1, after nitrogen blowing into the flask, add 4-(2H-benzotriazole-2-yl)-1,3-benzenediol and acetone, heat to 40°C, add chloroacetyl chloride, react for 7 hours, and remove the solvent under reduced pressure to obtain intermediate 1; S2, after nitrogen blowing into the flask, add intermediate 1, pyridine and dimethyl sulfoxide, heat to 60°C, add 1,3-propylenediamine, react for 3h, cool, and distill under reduced pressure to obtain intermediate 2; S3, after nitrogen blowing into the flask, add intermediate 2, triethylamine and dimethyl sulfoxide, raise the temperature to 70°C, add 2,6-di-tert-butyl-4-bromomethylphenol, react for 4 hours, cool, and distill under reduced pressure to obtain intermediate 3; S4, add intermediate 3 and DMF into a flask, heat to 65°C, add KH560, react for 3h, cool, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 4; S5. Mix the filler and deionized water in a flask, adjust the pH to 4, add intermediate 4 and DMF, raise the temperature to 65°C and react for 1 hour, cool, centrifuge, take the lower precipitate, ultrasonically disperse it in anhydrous ethanol, and dry to obtain a modified filler.
2. A high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The amount ratio of 4-(2H-benzotriazole-2-yl)-1,3-benzenediol, chloroacetyl chloride and acetone in step S1 is 34.1g:12.9mL:180mL; the amount ratio of intermediate 1, 1,3-propylenediamine, pyridine and dimethyl sulfoxide in step S2 is 39.5g:11.7mL:12.6mL:200mL; the amount ratio of intermediate 2, 2,6-di-tert-butyl-4-bromomethylphenol, triethylamine and dimethyl sulfoxide in step S3 is 36.7g:29.9g:16.7mL:220mL; the amount ratio of intermediate 3, KH560 and DMF in step S4 is 45g:15.5mL:220mL; the amount ratio of filler, intermediate 4, DMF and deionized water in step S5 is 42g:3g:20mL:250mL.
3. A high temperature resistant and anti-corrosion coating according to claim 2, characterized in that: The filler is a mixture of titanium dioxide, aluminum hydroxide, magnesium hydroxide and glass flakes in a mass ratio of 1:(0-0.5):(0.5-1):(3-5).
4. The high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, glycidyl ether epoxy resin, and alicyclic epoxy resin.
5. The high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The pigment is one or more of iron oxide red, phthalocyanine blue, phthalocyanine green G, carbon black and ultramarine.
6. The high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The curing agent is one or more of dicyandiamide, isophoronediamine and dodecanedicarboxylic acid dihydrazide.
7. The high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The accelerator is one or more of 1-methylimidazole, 2-ethyl-4-methylimidazole and 2-methylimidazole.
8. The high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The solvent is one or more of ethanol, acetone, butanone, N,N-dimethylacetamide and N,N-dimethylformamide.
9. The method for preparing a high temperature resistant and anti-corrosion coating according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight, then add epoxy resin, phenolic resin, modified filler, pigment and solvent into a disperser and stir thoroughly until mixed evenly, finally add curing agent and accelerator, stir thoroughly to obtain high temperature resistant and corrosion resistant coating.
Citation Information
Patent Citations
Functionalized nanometer silica with ultraviolet ray absorption function group grafted on surface, and preparation method thereof
CN103849165A
Preparation method of multifunctional synergistic antioxidative stabilizer
CN104530475A
Preparation method of anti-ultraviolet PVC drainage pipe
CN113308070A
Polypiperidylamine light stabilizer and preparation method thereof
CN116178346A
Anti-ultraviolet aging cable and preparation method thereof
CN118562236A
Cited By
Production process of rubber mould pressing foaming material
CN119978517A
Chemical-resistant glass based on nano-composite coating and application of chemical-resistant glass
CN121494348A
A chemical-resistant glass based on a nanocomposite coating and its application
CN121494348B